Penetapan Harga pada Pedagang Ayam Potong di Pasar Tradisional Kota Tembilahan - Nazori Madjid; Bahrul Ma’ani; Supyani Supyani; Habriyanto Habriyanto (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2022)
The purpose of this study was to analyze and describe why the pricing of broiler chicken traders in the traditional market of Tembilahan City has different prices. The research method uses a qualitative approach with the type of case study. Data was collected by observation, interviews, and documentation. Data analysis using John's model. W. Creswell, Miles and Huberman namely data reduction, data presentation, data verification, and drawing conclusions. Checking the validity of the data using data triangulation. The results of the study found that the different price fixing between the teak market, the Parit 11 market, the morning market, and the floating market in Tembilahan City were caused by; First, the profit per kilogram of broiler chicken differs from one market to another, so that the selling price is different even though the location is not far away and the producers of chicken are the same, the two consumer backgrounds in each market are not the same, namely the class society. low-income and high-class people, so that slaughtered chickens are still sold even at prices that are not the same from one market to another, the three strategic locations in one market and a less strategic location affect the price fixing by market traders.